Magnetron Sputtering as a Fabrication Method for a Biodegradable Fe32Mn Alloy - Jurgeleit, Till (Materials (Basel), 2017)
Biodegradable metals are a topic of great interest and Fe-based materials are prominent examples. The research task is to find a suitable compromise between mechanical, corrosion, and magnetic properties. For this purpose, investigations regarding alternative fabrication processes are important. In the present study, magnetron sputtering technology in combination with UV-lithography was used in order to fabricate freestanding, microstructured Fe32Mn films. To adjust the microstructure and crystalline phase composition with respect to the requirements, the foils were post-deposition annealed under a reducing atmosphere. The microstructure and crystalline phase composition were investigated by scanning electron microscopy, energy dispersive X-ray spectroscopy, and X-ray diffraction. Furthermore, for mechanical characterization, uniaxial tensile tests were performed. The in vitro corrosion rates were determined by electrochemical polarization measurements in pseudo-physiological solution. Additionally, the magnetic properties were measured via vibrating sample magnetometry. The foils showed a fine-grained structure and a tensile strength of 712 MPa, which is approximately a factor of two higher compared to the sputtered pure Fe reference material. The yield strength was observed to be even higher than values reported in literature for alloys with similar composition. Against expectations, the corrosion rates were found to be lower in comparison to pure Fe. Since the annealed foils exist in the austenitic, and antiferromagnetic γ-phase, an additional advantage of the FeMn foils is the low magnetic saturation polarization of 0.003 T, compared to Fe with 1.978 T. This value is even lower compared to the SS 316L steel acting as a gold standard for implants, and thus enhances the MRI compatibility of the material. The study demonstrates that magnetron sputtering in combination with UV-lithography is a new concept for the fabrication of already in situ geometrically structured FeMn-based foils with promising mechanical and magnetic properties.